Sports Injuries Prevention, Diagnosis, Treatment and Rehabilitation (Springer Berlin Heidelberg, 2015)
Sports Injuries: Prevention, Diagnosis, Treatment and Rehabilitation covers the whole field of sports injuries and is an up-to-date guide for the diagnosis and treatment of the full range of sports injuries. The work pays detailed attention to biomechanics and injury prevention, examines the emerging treatment role of current strategies and evaluates sports injuries of each part of musculoskeletal system. In addition, pediatric sports injuries, extreme sports injuries, the role of physiotherapy, and future developments are extensively discussed. All those who are involved in the care of patients with sports injuries will find this textbook to be an invaluable, comprehensive, and up-to-date reference